Susceptibility of patients receiving chemotherapy for haematological malignancies to scabies. Issue 3 (November 2020) - Hosoi, H.; Nishikawa, S.; Kida, Y.; Kishi, T.; Murata, S.; Iwamoto, M.; Toyoda, Y.; Yamada, Y.; Ikeda, T.; Sonoki, T.
Summary: Background: Scabies is a contagious dermatosis. The risk factors for its transmission remain unclear. A scabies outbreak, involving patients who were receiving chemotherapy for haematological malignancies, occurred at our hospital. Methods: The outbreak population was analysed to determine whether the incidence of scabies was higher among contact patients receiving chemotherapy for haematological malignancies. Results: A patient with crusted scabies was the index case, and 18 of 78 contact healthcare workers (HCWs) and 22 of 135 contact patients were diagnosed with classical scabies. Ten of 17 contact patients with haematological malignancies and 12 of 118 contact patients with other diseases were infected with scabies. The incidence rate was significantly higher among the patients with haematological malignancies ( P <0.001). The patients with haematological malignancies had a significantly lower mean minimum neutrophil count than those with other diseases (1159/μL vs 3761/μL, P =0.0012). Most haematological patients did not require special nursing assistance, suggesting that the higher incidence of scabies among these patients resulted from their immunodeficiency rather than greater skin-to-skin contact with infected HCWs. Conclusion: Our study suggests that patients receiving chemotherapy for haematological malignancies are more susceptible to scabies than patients with other diseases, and require stricter protection.